Heru Siswanto Model Pembelajaran Akidah Akhlak Dalam Membentuk Karakter Peserta Didik: (Studi di MA. Hidayatul Mubtadiin Tasikmadu, Malang, Jawa Timur, Indonesia) - Siswanto, Heru (MADINAH, 2014)
Schools as educational institutions that contribute in processing their students in inculcating noble values, norms (noble faith) in order to interact with good attitude and behavior and can distinguish which good values ​​and which are bad and can influence others berakidah morals with noble. For that in required process of implementation of appropriate learning. This study used qualitative research methods. In general, this qualitative research is described that the data is addressed as verbal data, research orientation understanding of good meaning refers to the characteristics of systematic relationships, conceptions, values, rules and abstraction formulation of understanding and emphasize the direct relationship between researchers and the world studied and prioritizing researchers as a key instrument. (Bakri, 2002: 50) Based on the results of research conducted by researchers in the field associated with learning model Akidah morals in shaping the character of learners in MA Hidayatul Mubtadiin Tasikmadu Malang, after the data obtained and discussed shows that the model of learning is understood and implemented by the teacher well, such as the lecture model, , assignment, discussion, habituation and exemplary While the character of the learners is good enough, if for example violate the violation of school rules.